2008
DOI: 10.1186/1745-6673-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Hydration status and physiological workload of UAE construction workers: a prospective longitudinal observational study

Abstract: BackgroundThe objective of the study was to investigate the physiological responses of construction workers labouring in thermally stressful environments in the UAE using Thermal Work Limit (TWL) as a method of environmental risk assessment.MethodsThe study was undertaken in May 2006. Aural temperature, fluid intake, and urine specific gravity were recorded and continuous heart rate monitoring was used to assess fatigue. Subjects were monitored over 3 consecutive shifts. TWL and WBGT were used to assess the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 21 publications
6
84
1
Order By: Relevance
“…It has been reported and observed that construction workers will self-pace, adjusting either the work rate or the duration of work intervals to maintain thermal balance and avoid heat related illness (Bates and Schneider, 2008;Taylor, 2006). In this regard, it has been shown that there was no difference in manual workers' heart rate responses under variate environmental heat stress and it is evident that self-pacing is a protective response to working in heat which does not require a highly informed workforce …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It has been reported and observed that construction workers will self-pace, adjusting either the work rate or the duration of work intervals to maintain thermal balance and avoid heat related illness (Bates and Schneider, 2008;Taylor, 2006). In this regard, it has been shown that there was no difference in manual workers' heart rate responses under variate environmental heat stress and it is evident that self-pacing is a protective response to working in heat which does not require a highly informed workforce …”
Section: Discussionmentioning
confidence: 88%
“…Therefore, it is important to deliver an active education program and promoting awareness of sufficient hydration and rehydration strategy to rebar workers. It has been shown that construction workers who begin work in well hydrated conditions are likely to maintain good levels of hydration during the shift (Bates and Schneider, 2008). Additionally, it is also useful to screen the hydration status of rebar workers at the worksite such as before work, during breaks, and after work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brake and Bates considered USG equal to 1.015 as a euhydrated state [7]. Thermal Work Limit (TWL), a newly developed index, incorporates all needed inputs and generates a single figure specifying a maximum work limit and is claimed to be "simple to use, less prone to interpretive error, reliable and far superior to currently recommended indices an indicator of thermal stress" [3]. All 5 main parameters that define thermal environment, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…air temperature, radiant temperature, humidity, air movement, metabolic rate or human activity [35,36]. Also, numerous studies across the world have shown the impacts of hot working environments on the working population [37][38][39][40][41][42][43]. The choice of which material or combination of materials is used depends on a wide variety of factors.…”
Section: Introductionmentioning
confidence: 99%